Effects of storage period and egg weight of Japanese quail eggs on hatching results (short communication) - Seker, I; Kul, S; Bayraktar, M (Archiv Fur Tierzucht, 2005)
This study was undertaken to determine the effects of storage period and egg weight of hatching eggs of Japanese quails on fertility, hatchability results. Eggs were obtained 150 females quails, all at 15 weeks of age. A total of 1942 hatching eggs were separated into 3 groups as light-weight (9.50-10.50 g), medium-weight (10.5 - 11.50 g), and heavy-weight (11.5 1-12.50 g). Based on storage period, eggs were divided into 5 groups as group 1 (0-3 days), group 2 (4-6 days), group 3 (7-9 days), group 4 (10-12 days), and group 5 (13-15 days). The influence of storage period on hatchability of fertile eggs and early, middle, and late period embryonic mortality rates was found significant (P<0.01). The effect of egg weight on fertility rate, hatchability of fertile eggs and early embryonic mortality was significant (P<0.05, P<0.01). The significant differences between storage period groups were observed in hatchability of fertile eggs. The differences between egg weight groups for fertility rate, hatchability of fertile eggs and early embryonic mortality was significantly higher in light weight group than the other egg weight groups. Results of this study concluded that a 12 day pre-incubation storage of hatching eggs of Japanese quails did not appreciably affect hatching parameters. Use of medium or heavy weight eggs for hatching may reduce early embryonic mortality rate.
Keywords: storage period; egg weight; hatchability; embryonic mortality; quail